Tunable and high-color-rendering white light emissions in full visible spectral range in Ag-aggregates/Sm3+ co-doped germanate glass fluorophors. Issue 16 (15th August 2022) - Zhang, Yuhang; Chen, Baojiu; Zhang, Xizhen; Zhang, Jinsu; Xu, Sai; Yu, Hongquan; Li, Xiangping; Cao, Yongze; Wang, Yichao; Wang, Xin; Gao, Duan; Sha, Xuzhu; et al.
Abstract: To achieve a tunable and high-color-rendering white light emission in full visible spectral range, the Ag-aggregates/Sm 3+ co-doped germanate glass fluorophors were prepared by a melt-quenching method. Under the excitation of different wavelengths, the intense broadband emissions covering full visible spectral range from blue to red were gained in the germanate glasses only containing Ag-aggregates. From the optical spectral analyses, it was found that with increasing the excitation wavelengths, the emission peak position exhibits red-shift. However, the red component in the emission spectra is still of relative lack for realizing high quality white light, therefore Sm 3+ was introduced as co-dopant to supply the red spectral component. In this way, a series of chroma-tunable and full-color-emitting white lights with color coordinates from (0.26, 0.25) to (0.30, 0.32) were successfully realized based on adjusting the excitation wavelengths and Sm 3+ concentration. Particularly, the color rendering index (CRI) up to 97.6 was achieved. Furthermore, the luminescence thermal stability of Ag-aggregates/Sm 3+ co-doped germanate glass fluorophors was investigated based on the Arrhenius model, and the corresponding Δ E values for Ag aggregates and Sm 3+ emissions were confirmed to be 0.25 and 0.19 eV, respectively. In addition, a temperature sensing model was established based on the luminescence intensity ratio of Ag-aggregates to Sm 3+, and the thermochromatic property of Ag-aggregates/Sm 3+ co-doped germanate glasses was also evaluated. It was found that the luminescence color coordinates of Ag-aggregates/Sm 3+ co-doped glass fluorophors always lie in the white light region when the sample temperature increases from 301 to 693 K, thus indicating that Ag-aggregates/Sm 3+ co-doped glass fluorophors have potential application in solid-state lighting sources as a single-component white lighting material.